Indonesian Culinary Application System Design with UML Method - Hindarto, Djarot (Information Technology and Science (ITScience), 2023)
Indonesia has an important role as a country that produces various high-quality culinary items. Indonesia, with its plethora of natural resources and cultural diversity, can generate a wide range of culinary goods, including traditional foods and beverages as well as modern culinary inventions. Natural and cultural potentials are the foundation for the development of exceptional food and beverages in a country manufacturing culinary products. However, numerous issues with marketing are not global enough, even though Indonesian culinary items should be able to compete with well-known food products. Information technology and the internet have altered the culinary business scene in Indonesia, making it easier for local culinary products to obtain worldwide market share. This article investigates how the existence of information technology and the internet has opened up new avenues for Indonesian culinary manufacturers to broaden their marketing reach. Indonesian culinary items can now be accessed by consumers worldwide via an online platform, removing geographical barriers and presenting substantial economic growth possibilities. This study created an application system to advertise culinary products, with the first steps focusing on designing application systems. The Unified Modeling Language technique is used to create the culinary application system. This procedure aids in visualizing the system's structure, and interactions deployment. As a result, development teams and stakeholders have a more structured design and a better grasp of the system. Unified Modeling Language is quickly becoming a valuable tool for supporting thorough collaboration and documentation in application development.